Building safety and security through architectural design. - Sikta Singh; Shashi Saxena (International Journal of Urban Design and Development, 2023)
Everyone has the right to life, liberty, and security of person. Security is a type of protection from or say it is the resilience against any type of potential harm of other unwanted force or threat that is caused by others, by restraining the freedom of others to act. Beneficiaries in this study of technical referents of security in any building may be persons and social groups, objects, and institutions, ecosystems, or any other entity or phenomenon endangered by changes that are sudden. A building is called smart when It is capable of resisting all types of endangered changes and protecting the people in its building envelope. Technology is one such medium that is prevalent nowadays. Smart buildings are intelligent buildings that provide smart facilities that use information and communications technology-based systems with services and technology to customize the overall building performance
Keywords: Buildings; endangered; information; institutions; resilience